Effects of hypercapnia / ischemia and dissection on the rat brain metabolome. (June 2022) - Sylvestre, Duncan A.; Otoki, Yurika; Metherel, Adam H.; Bazinet, Richard P.; Slupsky, Carolyn M.; Taha, Ameer Y.
Abstract: It is known that brain energy metabolites such as ATP are quickly depleted during postmortem ischemia; however, a comprehensive assessment on the effects of preceding hypercapnia/ischemia and the dissection process on the larger brain metabolome remains lacking. This study sought to address this unknown by measuring aqueous metabolites impacted by hypercapnia/ischemia and brain dissection using Nuclear Magnetic Resonance. Metabolites were measured in rats subjected to 1) high energy head-focused microwave irradiation (control group); 2) CO2 –induced hypercapnia/ischemia followed by immediate microwave irradiation; 3) CO2 followed by decapitation and then microwave irradiation ∼6.4 min later, to simulate a postmortem interval equivalent to typical dissection times; and 4) CO2 –induced hypercapnia/ischemia followed by dissection within ∼6 min (no microwave fixation) to test the effects of brain dissection on the metabolome. Compared to control rats subjected to head-focused microwave irradiation, concentrations of high-energy phosphate metabolites and glucose were significantly reduced, while β-hydroxybutyrate and lactate were increased in rats subjected to all other treatments. Several amino acids and neurotransmitters (GABA) increased by hypercapnia/ischemia and dissection. Sugar donors involved in glycosylation decreased and nucleotides decreased or increased following hypercapnia/ischemia and dissection. sn-Glycero-3-phosphocholine decreased and its choline byproduct increased in all groups relative to controls, indicating postmortem changes in lipid turnover. Antioxidants increased following hypercapnia/ischemia but decreased to control levels following dissection. This study demonstrates substantial post-mortem changes in brain energy and glycosylation pathways, as well as protein, nucleotide, neurotransmitter, lipid, and antioxidant turnover due to hypercapnia/ischemia and dissection. Changes in phosphate donors, glycosylation and amino acids reflect post-translational modification and protein degradation processes that persist post-mortem. Microwave irradiation is necessary for accurately capturing in vivo brain metabolite concentrations. Highlights: Postmortem effects of ischemia and dissection on rat brain metabolites were tested. Ischemia/dissection depleted brain energy metabolites relative to microwave fixation. Amino acids and neurotransmitters increased suggesting proteolysis and turnover. Sugar donors, lipids, antioxidants and nucleotides increased or decreased. Microwave fixation is necessary to limit postmortem changes in ischemia/dissection.